2022
DOI: 10.1155/2022/2187696
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Lactoferrin Induces Cell Death in Human Prostate Cancer Cells

Abstract: Bovine lactoferrin (bLf) is a multifunctional protein widely associated with anticancer activity. Prostate cancer is the second most frequent type of cancer worldwide. This study was aimed at evaluating the influence of bLf on cell viability, cell cycle progression, reactive oxygen species (ROS) production, and rate of apoptosis in the human prostate cancer cell line (DU-145). MTT assay and trypan blue exclusion were used to analyze cell viability. Morphological changes were analyzed through optical microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The interest in LF as an anticarcinogenic strategy is supported by its capacity to bind free iron, prevent the formation of toxic species, modulate cytokine secretion, regulate the immune–inflammatory response, participate in cell growth, promote apoptosis, and activate NK cells [ 54 , 55 , 56 , 57 ]. Previous studies have shown that iron chelators prevent the progression of estrogen-dependent neoplasms by limiting the bioavailability of free iron, which can damage cellular DNA and promote tumor cycling, linking the antitumor properties of LF to its action as an iron scavenger [ 58 ].…”
Section: Lactoferrin Biological Functionsmentioning
confidence: 99%
“…The interest in LF as an anticarcinogenic strategy is supported by its capacity to bind free iron, prevent the formation of toxic species, modulate cytokine secretion, regulate the immune–inflammatory response, participate in cell growth, promote apoptosis, and activate NK cells [ 54 , 55 , 56 , 57 ]. Previous studies have shown that iron chelators prevent the progression of estrogen-dependent neoplasms by limiting the bioavailability of free iron, which can damage cellular DNA and promote tumor cycling, linking the antitumor properties of LF to its action as an iron scavenger [ 58 ].…”
Section: Lactoferrin Biological Functionsmentioning
confidence: 99%
“…Caco-2 cells were placed into two-well chamber slides (BD Falcon, Miami, FL, USA) at a density of 104 cells per square centimeter and cultured using complete DMEM culture medium. On the second day (cultured for 24 h), cellular monolayers were subjected to a preliminary incubation with 1 mL of HBSS (Hank's Balanced Salt Solution) for a duration of 15 min at a temperature of 37 • C. After equilibrating, the medium was replaced with 1 mL suspensions of FITC-bLf, FITC-bLf-loaded unmodified, chitosan-, and pectin-modified SLPs (10 µg/mL in HBSS), followed by incubation for 1 h at 37 • C [42]. Subsequently, the cells underwent eight rounds of cold sterile PBS (pH 7.4) washing.…”
Section: Confocal Microscopy Analysismentioning
confidence: 99%
“…Lactoferrin (LF) is an iron‐binding glycoprotein primarily found in milk and other body secretions, which has been consolidated as a remarkably beneficial protein for its antimicrobial (Acosta‐Smith et al., 2017 ), antiviral (Hu et al., 2021 ), antifungal (Manzoni et al., 2012 ), anti‐inflammatory (Goulding et al., 2021 ), and immune stimulatory function (Siqueiros‐Cendón et al., 2014 ). Bovine lactoferrin (bLF) (80 kDa) has in vitro and in vivo anticancer activity against several types of cancer (Chea et al., 2018 ; Gibbons et al., 2015 ; Haney et al., 2012 ; Li et al., 2017 ; Luzi et al., 2017 ; Rocha et al., 2022 ; Sun et al., 2012 ; Wolf et al., 2003 ; Zhang et al., 2015 ), and it induced a reduction in colorectal cancer polyps, improvement in patient quality of life, and reduction in toxic side effects of chemotherapy drugs (Kozu et al., 2009 ; Moastafa et al., 2014 ). This anticancer activity of bLF has been attributed to inhibition of cell viability by disruption of the cell membrane, induction of cell cycle arrest, apoptosis, or iron deprivation (Fujita et al., 2004 ; Gibbons et al., 2015 ; Li et al., 2011 ; Luzi et al., 2017 ; Ramírez‐Sánchez et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…lactoferrin (bLF) (80 kDa) has in vitro and in vivo anticancer activity against several types of cancer (Chea et al, 2018;Gibbons et al, 2015;Haney et al, 2012;Li et al, 2017;Luzi et al, 2017;Rocha et al, 2022;Sun et al, 2012;Wolf et al, 2003;Zhang et al, 2015), and it induced a reduction in colorectal cancer polyps, improvement in patient quality of life, and reduction in toxic side effects of chemotherapy drugs (Kozu et al, 2009;Moastafa et al, 2014). This anticancer activity of bLF has been attributed to inhibition of cell viability by disruption of the cell membrane, induction of cell cycle arrest, apoptosis, or iron deprivation (Fujita et al, 2004;Gibbons et al, 2015;Li et al, 2011;Luzi et al, 2017;Ramírez-Sánchez et al, 2021).…”
mentioning
confidence: 99%